Self-Assessment Development in Physical Education Learning on Under Service Materials Using JotForm - Dina Zulfa; Nurul Ihsan (Halaman Olahraga Nusantara : Jurnal Ilmu Keolahragaan, 2021)
The aim of this research is to develop self-assessment in physical education, sports and volleyball, using an online form jotform for class X at SMA N 1 Batipuh. Based on observations made by researchers at SMA N 1 Batipuh, so that students are able to do a self-assessment on the physical education of the lower service volleyball which is difficult to understand the material and the achievement is not optimal and knows mistakes, making it easier for the teacher to make assessments and subsequent actions. This type of research is the development of the IDI model. The research subjects were 3 FIK UNP lecturers, one physical education teacher, and 31 students. The object of self-assessment research in the physical education of volleyball underserved using the jotform. The validity and practicality research data obtained directly are 86.76% very feasible, the practicality of teachers is 92.76% very feasible and practicality students for 90.77% are very valid.